Insulin-Attenuated Inflammatory Response of Dendritic Cells in Diabetes by Regulating RAGE-PKCβ1-IRS1-NF-κB Signal Pathway: A Study on the Anti-Inflammatory Mechanism of Insulin in Diabetes - Liding Zhao; Ya Li; Qingbo Lv; Min Wang; Yi Luan; Jiale Song; Guosheng Fu; Junbo Ge; Yunzeng Zou; Wenbin Zhang (Journal of Diabetes Research)
Background. Diabetes is associated with chronic inflammation, and dendritic cells (DCs) have proinflammatory effect in diabetes. The anti-inflammatory effect of insulin on diabetes is not entirely clear. The study aims to examine insulin-induced effects on the inflammatory response in DCs. Methods. Twenty-one C57BL/6 mice were divided into 3 groups. Streptozotocin was injected into the diabetic mice model. The bone marrow-derived DCs (BMDCs) were obtained from C57BL/6 mice. CD83, CD86, and type II major histocompatibility complex (MHC-II) of BMDCs were measured by flow cytometry. The fluctuations in the RNA levels of cytokines and chemokines were analyzed by quantitative RT-PCR. The concentrations of IFN-γ and TNF-α were calculated using ELISA kits, and the proteins were detected using western blot. Results. In CD11c+ DCs derived from the spleens with hyperglycemia, the expression of CD83 and CD86 in diabetic mice was significantly upregulated, coupled with a higher secretion level of cytokines and chemokines, and increased phosphorylation of NF-κB and IκB. Insulin therapy was found to have a reversal effect on the inflammatory response and immune maturation in DCs. In AGEs-BSA-stimulated BMDCs, insulin repressed the immune maturation and downregulated the expression of RAGE, phospho-PKCβ1, and serine phospho-IRS1 in an adose-dependent manner. Such effects can be abolished by PMA, but not IR-neutralizing antibody. AGEs-BSA-induced BMDCs immune maturation was inhibited by the neutralizing antibody of RAGE, the PKCβ1 inhibitor, or the IRS1 siRNA. Conclusions. Insulin has the capability of attenuating the inflammatory response of DCs in diabetes, partly through the downregulation of RAGE expression followed by the inhibition of PKCβ1 phosphorylation and IRS1 serine phosphorylation, resulting in the inactivation of IR binding-independent NF-κB. This might partly explain the antiatherogenic effect of insulin on diabetes.